The Dynamics of Foreign Direct Investment in BRICS Countries - Tsaurai, Kunofiwa (Journal of Economics and Behavioral Studies, 2017)
Recent studies which investigated the determinants of foreign direct investment (FDI) in BRICS include Hsin-Hong and Shou-Ronne (2012), Nandi (2012), Jadhav (2012), Darzini and Amirmojahedi (2013), Nischith (2013), Ho et al. (2013), Kaur et al. (2013) and Priya and Archana (2014). The findings from these studies shows lack of consensus and confirm that a list of agreeable determinants of FDI in BRICS countries is still an unsettled matter. This paper was therefore initiated in order to contribute to the debate on the discourse on FDI determinants in BRICS countries.This paper deviates from earlier similar studies in five ways: (1) uses most recent data, (2) is the first to investigate whether a combination of financial development, trade openness, human capital, economic growth and inflation influence FDI in BRICS countries, (3) uses different proxies of the variables that affect FDI, (4) employed both fixed effects and pooled ordinary least squares (OLS) approaches and (5) used a stacked data approach.The results of the study showed that economic growth, trade openness and exchange rate stability positively impacted on FDI, financial development positively influenced FDI under fixed effects, FDI was positively influenced by human capital development using the pooled OLS and inflation negatively affected FDI in line with literature. Taking into account these findings, this study urges BRICS to implement policies that increase financial sector efficiency and economic growth, maintain stable exchange rates, keep inflation rates at lower levels, enhance trade openness and human capital development in order to increase FDI inflows.